Maternal Multivitamin Intake, Plasma Folate and Vitamin B12 Levels and Autism Spectrum Disorder Risk in Offspring. Issue 1 (6th October 2017) - Raghavan, Ramkripa; Riley, Anne W.; Volk, Heather; Caruso, Deanna; Hironaka, Lynn; Sices, Laura; Hong, Xiumei; Wang, Guoying; Ji, Yuelong; Brucato, Martha; Wahl, Anastacia; Stivers, Tom; et al.
Abstract: Background: To examine the prospective association between multivitamin supplementation during pregnancy and biomarker measures of maternal plasma folate and vitamin B12 levels at birth and child's Autism Spectrum Disorder (ASD) risk. Methods: This report included 1257 mother–child pairs, who were recruited at birth and prospectively followed through childhood at the Boston Medical Center. ASD was defined from diagnostic codes in electronic medical records. Maternal multivitamin supplementation was assessed via questionnaire interview; maternal plasma folate and B12 were measured from samples taken 2–3 days after birth. Results: Moderate (3–5 times/week) self‐reported supplementation during pregnancy was associated with decreased risk of ASD, consistent with previous findings. Using this as the reference group, low (≤2 times/week) and high (>5 times/week) supplementation was associated with increased risk of ASD. Very high levels of maternal plasma folate at birth (≥60.3 nmol/L) had 2.5 times increased risk of ASD [95% confidence interval (CI) 1.3, 4.6] compared to folate levels in the middle 80th percentile, after adjusting for covariates including MTHFR genotype. Similarly, very high B12 (≥536.8 pmol/L) showed 2.5 times increased risk (95% CI 1.4, 4.5). Conclusion: There was a 'U shaped' relationship between maternal multivitamin supplementation frequency and ASD risk. Extremely high maternal plasma folate and B12 levels at birth were associated with ASD risk. This hypothesis‐generating study does not question the importance of consuming adequate folic acid and vitamin B12 during pregnancy; rather, raises new questions about the impact of extremely elevated levels of plasma folate and B12 exposure in‐utero on early brain development.